2019
DOI: 10.1029/2018jb016572
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic and Postseismic Deformation of the 2016 MW 6.2 Lampa Earthquake, Southern Peru, Constrained by Interferometric Synthetic Aperture Radar

Abstract: We use Sentinel-1 radar imagery to explore the coseismic and postseismic surface displacements associated with the 2016 M W 6.2 Lampa earthquake in southern Peru. Based on coseismic interferograms, the preferred slip model links to a blind south southeast striking, south southwest dipping normal fault with a shallow dip (45.2°) and a peak slip of 0.71 m at depth~5.3 km, which is consistent with seismic solutions. Postseismic interferograms, derived from two tracks of the Sentinel-1A/B satellites using a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 107 publications
(165 reference statements)
2
10
1
Order By: Relevance
“…After an initial period of afterslip, creep on this fault continues linearly, in tandem with the continuing inflation ( Figures 8 and 10). Although long-lived afterslip on a normal fault is not unprecedented in this tectonic setting, the longest recorded afterslip in this region lasted for only one year [Xu et al, 2019], far less than the 5+ years of creep observed in this study. For the Hayward fault in California, Schmidt and Bürgmann [2008] found that, after an earthquake, creep resumed when the ratio of shear to normal stress matched the value of this ratio prior to the earthquake.…”
Section: Fault Creep At Sabancayacontrasting
confidence: 63%
“…After an initial period of afterslip, creep on this fault continues linearly, in tandem with the continuing inflation ( Figures 8 and 10). Although long-lived afterslip on a normal fault is not unprecedented in this tectonic setting, the longest recorded afterslip in this region lasted for only one year [Xu et al, 2019], far less than the 5+ years of creep observed in this study. For the Hayward fault in California, Schmidt and Bürgmann [2008] found that, after an earthquake, creep resumed when the ratio of shear to normal stress matched the value of this ratio prior to the earthquake.…”
Section: Fault Creep At Sabancayacontrasting
confidence: 63%
“…After an initial period of afterslip, creep on this fault continues linearly, in tandem with the continuing inflation (Figures and ). Although long‐lived afterslip on a normal fault is not unprecedented in this tectonic setting, the longest recorded afterslip in this region lasted for only 1 year (Xu et al, ), far less than the 5+ years of creep observed in this study. For the Hayward fault in California, Schmidt and Bürgmann () found that, after an earthquake, creep resumed when the ratio of shear to normal stress matched the value of this ratio prior to the earthquake.…”
Section: Discussionmentioning
confidence: 47%
“…This postseismic behavior shares features similar to many experimental results (Chambon et al., 2006; Cornelio et al., 2019; Jia et al., 2020; Nielsen, Spagnuolo, Violay, et al., 2016; Ohnaka & Shen, 1999). Postseismic slip (or deformation) also has been widely reported in natural earthquakes, for example (Hussain et al., 2018; Lin et al., 2013; Perfettini & Avouac, 2004; Twardzik et al., 2019; Xu et al., 2019). Due to the different slip weakening behavior, Type I events show smaller breakdown slip displacement than Type II events (10 vs. 15 μm; Figure S8a in Supporting Information ).…”
Section: Resultsmentioning
confidence: 98%